Penerapan Terapi Bermain Mewarnai dengan Kecemasan Anak Usia Pra Sekolah - Masita Dihuma; Andi Arniyanti; Sanghati Sanghati (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
Introduction: A preschool-age child considers hospitalization to be a scary experience; when a young child is hospitalized, usually, he will not be allowed to move much and will have to rest much treatment in the hospital is called hospitalization. Method: Qualitative research using case studies in the form of case reports. Results: After being given coloring play therapy, the client's results are no longer tense, lethargic, no longer agitated, and she is categorized as experiencing mild anxiety. Conclusion: There was a decrease in anxiety levels in preschool-aged children hospitalized before and after being given play therapy. Nurses need to apply coloring play therapy in preschool-aged children experiencing anxiety.